A Contingency Model of Boards of Directors and Firm Innovation: The Moderating Role of Firm Size. (9th February 2012) - Zona, Fabio; Zattoni, Alessandro; Minichilli, Alessandro
Abstract : This study asserts that the effects of board characteristics on firm innovation need to be evaluated with reference to contingency variables. A literature review suggests that relatively few studies adopt a contingency view when examining the outcomes of boards of directors. This study examines the influence on firm innovation of characteristics such as board size, outsider ratio and board diversity, and suggests that their influence is contingent upon firm size. The model is tested on a sample of Italian companies and finds support for the contingency hypothesis. This study advances research on boards of directors by emphasizing the importance of context.